1980
DOI: 10.1051/rnd:19800510
|View full text |Cite
|
Sign up to set email alerts
|

Les stimulations olfactives dans les relations entre l'enfant et la mère

Abstract: Summary. Olfactory stimulations in mother-child relations.In this paper, we report new data on mutual olfactory recognition between mother and child.Newborn infants were filmed since birth. When awakening in the mother's room at the Clinical Hospital, they were confronted with a cotton pad impregnated with diverse secretions of the mother and a cotton pad impregnated with the same secretions of another mother or a pad with no specific odour. We used a double-blind technique. By analyzing the films, frame by fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(54 citation statements)
references
References 2 publications
2
49
0
2
Order By: Relevance
“…Odor cues from newborns are salient to their mothers (Kaitz et al, 1987). Mothers can distinguish the odor of their own newborn baby from that of other newborns (Schaal et al, 1980;Kaitz et al, 1987;Chiarelli, 2001). Experiments also have demonstrated that adults can recognize gender and individuality of non-related children (Ligabue Stricker, 1991;Chiarelli, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Odor cues from newborns are salient to their mothers (Kaitz et al, 1987). Mothers can distinguish the odor of their own newborn baby from that of other newborns (Schaal et al, 1980;Kaitz et al, 1987;Chiarelli, 2001). Experiments also have demonstrated that adults can recognize gender and individuality of non-related children (Ligabue Stricker, 1991;Chiarelli, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Children usually prefer parts of clothes that have been in contact with the axilla and worn by their own mothers to clothes worn by other mothers (Schaal et al, 1980). Thus, pheromones seem to have a fundamental role in the mechanism of mother-child identification (Porter et al, 1983;Porter and Winberg, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…A capacidade precoce de reconhecimento individual também é sugestiva da importância da vinculação individualizada. Só para se ter uma idéia, na primeira semana de vida os bebês já são capazes de identifi car e preferir a mãe a estranhos, pelo odor (Schaal et al, 1980), pela voz (MacFarlane, 1975 e pela face (Field, Cohen, Garcia, & Greenberg, 1984).…”
Section: A Agenda Do Bebêunclassified
“…Newborns' odour cues are salient to their mothers and mothers are able to discriminate their own newborn baby's odour from another newborn baby (Schaal et al, 1980). Recognition of infant's odour by mothers, using clothing worn by the infant, can be shown even within the first week of birth (Fleming et al, 1995) or even the first 2 days (Porter, Cernoch and McLaughlin, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Very young infants can identify their mothers using smell (Macfarlane, 1975;Varendi and Porter, 2001). For example, Schaal et al (1980) showed that infants orientate towards parts of clothes that have had contact with the axillae and worn by their own mothers compared to clothes worn by other mothers. However, most research attention has focused on infants' interest in mother's breast odour.…”
Section: Introductionmentioning
confidence: 99%